Robust multi-H2 output-feedback approach to aerial refuelling automation of large aircraft via linear matrix inequalities - Claase, Etienne H. (Stellenbosch : Stellenbosch University, 2013)
Thesis (MScEng)--Stellenbosch University, 2013.